Analysis of the Application of AI Technology for Radio and Television Broadcasting under Computer Networks - Luo, Hao (Journal of Artificial Intelligence and Information, 2025)
The times are constantly progressing and science and technology are developing rapidly. Among them, computers and networks have become an important outcome of scientific and technological development, bringing new directions for the reform of radio and television multimedia technology. Compared with traditional media communication methods, radio and television multimedia communication under computer network has a new direction, which can abandon the geographical and time limitations of traditional media transmission methods and greatly broaden the transmission channels of radio and television media technology. People nowadays prefer the new computer network for radio and television multimedia technology. This greatly promotes the innovation and development of radio and television multimedia technology, can attract more people to interest in radio and television media, and further promotes improvement and improvement of radio and TV multimedia technology.